2019
DOI: 10.1111/pim.12616
|View full text |Cite
|
Sign up to set email alerts
|

Induction of tolerogenic properties by Anisakis larval antigens on murine dendritic cells

Abstract: Summary Aims The objective of this work is to investigate whether Anisakis simplex larval antigens present immunomodulatory properties by the induction of tolerogenic dendritic cells (DCs) from two strains of mice (BALB/c and C57BL/6J). Methods and Results We used mouse bone marrow‐derived DCs. We determined their antigen‐presenting ability by expression of membrane markers (MHC I and MHC II, CD80, CD86) and intracellular expression levels of IL‐10 and IL‐12 cytokines. We also analysed whether stimulation with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Anisakidosis is an emerging fish-borne zoonosis of major public health concern and despite the increasing concern on the impact of the disease, which is thought to be largely underestimated; our current understanding of the mechanisms of infection and clinical disease in humans is limited. Recently, some attempts have been made to clarify some aspect of infection using in-vivo tests with animal models [19] or to explore human immune responses using in-vitro systems [33], suggesting a general strong induction of immune reaction. However, studies on comparison of pathogenic anisakid species versus phylogenetically related non-pathogenic nematodes were thus far unavailable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anisakidosis is an emerging fish-borne zoonosis of major public health concern and despite the increasing concern on the impact of the disease, which is thought to be largely underestimated; our current understanding of the mechanisms of infection and clinical disease in humans is limited. Recently, some attempts have been made to clarify some aspect of infection using in-vivo tests with animal models [19] or to explore human immune responses using in-vitro systems [33], suggesting a general strong induction of immune reaction. However, studies on comparison of pathogenic anisakid species versus phylogenetically related non-pathogenic nematodes were thus far unavailable.…”
Section: Discussionmentioning
confidence: 99%
“…The draft genome sequence was available for A. simplex [23,32] and we assumed that was related to the species A. simplex sensu stricto. Raw reads generated for the three taxa HA, AS and AP were mapped to the existing genome assembly sequences [23,33]. The highest percentages of mapping were obtained for transcriptomes belonging to the same genus.…”
Section: The Hysterothylacium Aduncum Anisakis Simplex Sensu Strictomentioning
confidence: 99%
“…In our previous work, we demonstrated that even though murine DCs stimulated in vitro with A. simplex larval antigens did not reach a complete activated phenotype, they showed ability to present antigens to T cells and cause polarization. (1) Likewise, Napoletano et al observed that Anisakis pegreffii generated human DCs with an impaired phenotype as demonstrated by low expression of HLAII-DR and CD86 costimulatory molecules. (9) In this work, co-cultivation of mouse splenocytes with DCs previously stimulated with A. simplex larval antigens caused the expansion of T regs .…”
Section: Discussionmentioning
confidence: 99%
“…(8) Different stimuli were employed: ES (0.012 µg/mL) or CE (50 µg/mL) for 24 hours (CO 2 5%, 37ºC). (1) A control of DCs cultured in medium without antigens was included in all the experiments. All experiments were performed in triplicate wells for each condition and repeated at least three times.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation